3D Bioprinting Technology – One Step Closer Towards Cardiac Tissue Regeneration - Chingale, Mira; Cheng, Ke; Huang, Ke (Frontiers in Materials, 2022)
Cardiovascular disease is one of the leading causes of death across the globe. Heart transplantation has been used for end-stage heart failure patients. However, due to the lack of donors, this treatment option usually depends on multiple variables and the result varies due to immunological issues. 3D bioprinting is an emerging approach for in vitro generation of functional cardiac tissues for drug screening and cardiac regenerative therapy. There are different techniques such as extrusion, inkjet, or laser-based 3D printing that integrate multiple cell lines with different scaffolds for the construction of complex 3D structures. In this review, we discussed the recent progress and challenges in 3D bioprinting strategies for cardiac tissue engineering, including cardiac patches, in vitro cardiac models, valves, and blood vessels.